Survival After Minimally Invasive vs. Open Radical Hysterectomy for Cervical Cancer: A Meta-Analysis - Wang, Yizi; Li, Bo; Ren, Fang; Song, Zixuan; Ouyang, Ling; Liu, Kuiran (Frontiers in Oncology, 2020)
Background: The comparison of survival outcomes between minimally invasive surgery and open surgery for cervical cancer patients remains controversial. We evaluated the survival outcomes of cervical cancer patients who underwent different surgical approaches. Methods: A literature search was performed in PubMed, Embase, and Cochrane databases up to February 2020, using the MESH terms “minimally invasive surgical procedures” and “Uterine Cervical Neoplasms”. Included were all original comparative studies and trials both published and unpublished in English that were related to minimally invasive surgery and open surgery for cervical cancer patients with International Federation of Gynecology and Obstetrics (FIGO) 2009 stage < IIB. Begg’s and Egger’s regressions were used to evaluate publication bias. Results: This meta-analysis included 28 studies enrolling 18,961 patients with cervical cancer. The overall analyses indicated that cervical cancer patients with FIGO 2009 stage < IIB who underwent minimally invasive surgery had a lower rate of OS (HR = 1.43, 95% CI 1.06–1.92, P = 0.019) and DFS (HR = 1.50, 95% CI 1.21–1.85, P < 0.001) than those who underwent open surgery. Moreover, minimally invasive surgery could lower OS (HR = 2.30, 95% CI 1.50–3.52, P < 0.001) and DFS (HR = 1.94, 95% CI 1.36–2.76, P < 0.001) of cervical cancer patients with FIGO 2009 stage ≤ IB1 compared to open surgery. However, there were no significant differences in OS (HR = 1.07, 95% CI 0.65–1.76, P =0.801) and DFS (HR = 1.20, 95% CI 0.65–2.19, P = 0.559) in patients with tumors < 2 cm between the two groups. Conclusions: Minimally invasive radical hysterectomy was associated with poor survival outcomes compared to open surgery. Patients with FIGO 2009 stage ≤ IB1 cervical cancer who underwent minimally invasive surgery have lower OS and DFS rates than those who underwent open surgery. Therefore, open surgery should be performed for cervical cancer patients. However, patients with tumors < 2 cm might take the most advantage of minimally invasive surgery without increasing poor prognosis. There are some limitations in the meta-analysis, which needs further high-quality multicenter studies to confirm and update our findings.